Development of an Offsite Prefabricated Rainscreen Façade System for Building Energy Retrofitting - Stefano Avesani; Annalisa Andaloro; Silvia Ilardi; Matteo Orlandi; Stefano Terletti; Roberto Fedrizzi (Journal of Facade Design and Engineering, 2020)
As the European building stock is in evident need of deep energy retrofitting to meet current European decarbonisation targets, the construction market calls for industrialised systems to boost massive renovations and activate economies of scale. The article outlines the development of an offsite fabricated system for building energy refurbishment through rainscreen façade elements. A focus is placed on such elements as they offer excellent system integration possibilities and the opportunity to boost the level of offsite fabrication, compared to other already industrialised façade systems, such as unitised façades. This research was carried out within the framework of BuildHEAT research project, funded by the European Union Horizon 2020 framework programme. The system concept is based on a systemic approach that combines energy efficiency, multifunctionality, integration of renewable energies, and ease of installation as design drivers. System development has rolled out through different phases, with an increased level of detail. During the schematic design phase, a set of different prefabricated façade panel dimensions were analysed. Afterwards, the component and system integration were assessed according to their impacts in terms of energy performance and fulfilment of mandatory technical requirements. As a last step, the most promising technical combinations underwent detailed design to verify construction feasibility and eliminate any bottlenecks during the fabrication phase. Results show that the proposed prefabricated solutions allowed: (i) simplified active system integration (photovoltaics, solar thermal, and building services), (ii) ease of installation on site, minimising the impact of renovation actions on occupants without compromising on final quality and reducing installation costs. Current limitations to extensive market diffusion of the system are related to two main aspects: (i) the need for on-site adjustments; and (ii) increased manufacturing costs compared to traditional external insulation interventions (e.g. ETICS). The current cost of the system (2020) is in the range of 3 - 1.5x the cost of, respectively, an ETICS or a vented rainscreen façade. However, as a next step, including the life-cycle perspective in the calculation, as well as accounting for economies of scale, the system will be evaluated, expecting a cost figure comparable to the rainscreen façade.